2007
DOI: 10.1016/j.im.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Process and technology challenges in swift-starting virtual teams

Abstract: Virtual teams often face tight schedules and a need to start quickly and perform instantly. The goal of our study was to enhance understanding of the challenges faced by such teams. We used time-interaction-performance theory as the framework for following the processes and functions within virtual teams working on a systems development task. Our study provided a detailed examination of the group process, applied to virtual teams working under time pressure. The challenges faced by virtual teams in such settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 26 publications
2
56
0
2
Order By: Relevance
“…In contrast, Munkvold and Zigurs (2007) found that cultural or language diversity within VT leads to differences in the members' thinking process, which will affect their performance negatively. Similarly, implementing VT could impact on trust negatively because of the geographical distance, difference in time zone, and other characteristics (Khazanchi and Zigurs, 2006).…”
Section: Benefits and Challenges Of Virtual Teamsmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, Munkvold and Zigurs (2007) found that cultural or language diversity within VT leads to differences in the members' thinking process, which will affect their performance negatively. Similarly, implementing VT could impact on trust negatively because of the geographical distance, difference in time zone, and other characteristics (Khazanchi and Zigurs, 2006).…”
Section: Benefits and Challenges Of Virtual Teamsmentioning
confidence: 86%
“…A large number of studies explored advantages and disadvantages relating to virtual teaming (Jarvenpaa and Leidner, 1999;May and Carter, 2001;Breankek and Martz, 2005;Anderson et al, 2007;Munkvold and Zigurs, 2007;Rosen et al, 2007;Lee-Kelley and Sankey, 2008;Ebrahim et al, 2009). VT often operate under such time-compressed schedules that they need to perform tasks and projects more rapidly than traditional face-to-face teams, because they do not work at the same time or place (Munkvold and Zigurs, 2007).…”
Section: Benefits and Challenges Of Virtual Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on numerous scholars' research and experiences in the online learning teams (Beranek & French, 2011;Bulu & Yildirm, 2008;Grzeda et al, 2008;Lee, Lee, Liu, Bonk, & Magjuka, 2009;Makani et al, 2016;Milman, 2015;Munkvold & Zigurs, 2007;Topchyan, 2015;Tseng et al, 2009), the following suggestions are proposed for instructional design and course facilitation when virtual teams are needed in online courses:…”
Section: Strategies To Form and Facilitate The Effective Virtual Learmentioning
confidence: 99%
“…The availability of a flexible and configurable based infrastructure is one of the main advantages of virtual teams. Virtual R&D teams often face tight schedules and the need to start quickly and perform instantly (Munkvold & Zigurs, 2007). Virtual teams may allow people to collaborate with more productivity at a distance (Gassmann & Von Zedtwitz, 2003a).…”
Section: Benefits Of Virtual Teamsmentioning
confidence: 99%